Influência da composição do gás na medição de vazão de tocha por tecnologia ultrassônica - Barcellos, Silvana Nunes (2017)
Among the many processes that compose the oil and natural gas production, the flare gas flow measurement using ultrasonic transit-time flow meter is going to be evaluated. The relevance of this analysis is the environmental issue intrinsic at flare gas flow measurement, associated with the fact that, in this flow, the fluid is not processed in a way to be conditioned for a defined specification. Specially, the effects caused by the variation in chemical composition of the natural gas at the flow profile correction factor, from the flow measurement by ultrasonic technology, are going to be evaluated. On the other hand, the flow profile correction factor calculation depends on the Reynolds number and, in general, the chemical composition and respective transport properties for Reynolds number estimation are set up at the flow meter only due to the manufacturing process. So, if in a certain production asset there is variation in the chemical composition of the over time or if new hydrocarbon wells starts to operate, the new chemical composition of the gas will not be reset at the flow meter and the Reynolds number will not be changed by the new properties, which characterizes a measurement error. The main goal of this study, therefore, is to evaluate the acceptable limits of variation of the thermo-physical properties to process the flow measurement in a regulated way, and to analyze the effect of this variation over time. In addition, an analysis about the estimation of the thermophysical properties is made. Considering that the legislation admits an uncertainty of 5% in the flaring process, among the studied cases, it was verified that the variation of the chemical composition of the natural gas causes a maximum flow variation of up to 15% of this maximum permissible uncertainty.